Shoe microclimate: An objective characterisation and subjective evaluation. (July 2019) - West, A.M.; Schönfisch, D.; Picard, A.; Tarrier, J.; Hodder, S.; Havenith, G.
Abstract: Shoe microclimate (temperature and humidity) has been suggested to contribute to perceptions of foot thermal comfort. However, limited data is available for perceptual responses in relation to shoe microclimate development both over time and within different areas of the shoe. This study evaluates perceptions of foot thermal comfort for two running shoes different in terms of air permeability in relation to temporal and spatial characteristics of shoe microclimate. The temporal characteristics of shoe microclimate development were similar for both shoes assessed. However, higher temperatures and humidity were observed for the less permeable shoe. Changes to shoe microclimate over time and differences between shoes were perceivable by the users. This study provides the most detailed assessment of shoe microclimate in relation to foot thermal comfort to date, providing relevant information for footwear design and evaluation. Highlights: The typical time course of shoe microclimate development is similar for shoes of different permeability. However in absolute terms, shoe microclimate temperature and humidity are affected by shoe permeability. Changes to shoe microclimate are perceivable by the wearer.